2002
DOI: 10.1073/pnas.251668398
|View full text |Cite
|
Sign up to set email alerts
|

The thioesterase domain from a nonribosomal peptide synthetase as a cyclization catalyst for integrin binding peptides

Abstract: Nonribosomal peptide synthetases responsible for the production of macrocyclic compounds often use their C-terminal thioesterase (TE) domain for enzymatic cyclization of a linear precursor. The excised TE domain from the nonribosomal peptide synthetase responsible for the production of the cyclic decapeptide tyrocidine A, TycC TE, retains autonomous ability to catalyze head-to-tail macrocyclization of a linear peptide thioester with the native sequence of tyrocidine A and can additionally cyclize peptide analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…In these cases, however, no clear picture emerges from the results obtained, which are quite different for the two Te domains examined. Overall, Srf-Te appears to be relatively specific for its natural substrate, surfactin (Tseng et al, 2002), whereas Tyc-Te has a rather broad substrate specificity (Kohli et al, 2002b), which has allowed its use, in combination with solid phase peptide synthesis, for the creation of libraries of cyclic molecules, which can then be screened for biological activities (Kohli et al, 2002a).…”
Section: Substrate Recognition By Te Domainsmentioning
confidence: 99%
“…In these cases, however, no clear picture emerges from the results obtained, which are quite different for the two Te domains examined. Overall, Srf-Te appears to be relatively specific for its natural substrate, surfactin (Tseng et al, 2002), whereas Tyc-Te has a rather broad substrate specificity (Kohli et al, 2002b), which has allowed its use, in combination with solid phase peptide synthesis, for the creation of libraries of cyclic molecules, which can then be screened for biological activities (Kohli et al, 2002a).…”
Section: Substrate Recognition By Te Domainsmentioning
confidence: 99%
“…Macrolactonization of Dap occurred with a k cat /K M only 1.3-fold reduced from that of the linear CDA analogue [113] and the ratio of cyclization to hydrolysis moderately dropped from 10:1 to 3:1 (Figure 6.5). This cyclization to hydrolysis ratio of Dap is still remarkable in comparison to studies with TycC TE, where simultaneous side chain alterations led to the predominance of hydrolysis over cyclization [75]. The efficient conversion to cyclic product may be caused by the Asp-D-Ala-Asp-Gly motif of the linear peptide precursor.…”
Section: Probing the Substrate Specificity Of Cda Cyclasementioning
confidence: 76%
“…Walsh and co-workers showed that Tyc TE was capable to cyclize peptide substrates, in which up to 7 of 10 cognate residues were simultaneously replaced [75]. Macrolactamization of these linear peptide precursors containing an integrated RGD sequence yielded potent [76], which could be used to further optimize macrocyclic peptide/polyketide natural products, such as the immunosuppressant rapamycin and the anticancer agent epothilone [77].…”
Section: Chemoenzymatic Approaches Towards Novel Cyclopeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kohli and coworkers showed that Tyc TE was capable to cyclize peptide substrates, in which up to 7 of 10 cognate residues were simultaneously replaced (66). Macrolactamization of these linear peptide precursors containing an integrated RGD sequence yielded potent inhibitors of ligand binding by integrin receptors, with cyclization and N-methylation being important contributors to nanomolar potency (Fig.…”
Section: Chemoenzymatic Approaches Toward Novel Cyclopeptidesmentioning
confidence: 99%